Oxidative Stress and Hemostatic Parameters in Patients With Nephrolithiasis Before and After Ureteroscopic Lithotripsy - Woźniak, Paweł; Kontek, Bogdan; Skalski, Bartosz; Król, Anna; Różański, Waldemar; Olas, Beata (Frontiers in Physiology, 2019)
Purpose In patients with nephrolithiasis, oxidative stress, especially lipid peroxidation is observed. Moreover, various invasive methods (including extracorporeal shock wave lithotripsy (ESWL)) for treatment of nephrolithiasis may induce not only the oxidative stress, but they may modulate hemostasis. The study was aimed to evaluate the oxidative damages of lipids and proteins in patients with nephrolithiasis (before and after ureteroscopic lithotripsy - URSL). The aim of the present study was also determine selected parameters of hemostasis in these patients. Methods 56 patients with nephrolithiasis and 49 healthy participants were included: 30 men and 26 women (for patient group); 27 men and 22 women (for healthy group). We measured the level of selected typical two biomarkers of oxidative modification of lipids (such as the production of thiobarbituric acid reactive substances (TBARS) and isoprostane concentration (8-isoPGF2)) and two biomarkers of oxidative damages of proteins (carbonylation and the level of thiol groups) in patients with nephrolithiasis (before and after URSL). The following parameters of hemostasis were measured: blood platelet count, the level of fibrinogen and D-dimer, and coagulation times (the activated partial thromboplastin time (APTT), prothrombin time (PT), and thrombin time (TT) of plasma). Results We observed the difference in the level of lipid peroxidation between patients before URSL and patients after URSL. The level of oxidative damages of plasma proteins from patients (after URSL) was not changed to compare to patients (before URSL). Neither, parameter of hemostasis was influenced by the presence of nephrolithiasis, nor by treatment with URSL. Conclusion We suggest URSL does not induce the oxidative modifications of plasma proteins and does not change hemostatic parameters in patients with nephrolithiasis.